KTB and the electrical conductivity of the crust - Haak, Volker; Kontny, Agnes (Journal of geophysical research. Solid earth, 1997)
The German Continental Deep Drilling Program (KTB) drilled two holes through crystalline rocks which are rich in both high-salinity fluids and graphite accumulated along shear zones. Analyses of a large number of borehole measurements yield models for the electrical resistivity of the upper and middle crust in the vicinity of the KTB holes. High observed resistivity, of more than 105 Ω m in the lowermost part of the 9000 m deep main hole, in a rather “wet” crust, indicates that effective mechanisms exist to cut down connections between fluid accumulations and therefore that fluids are not the likely cause of high-conductivity anomalies. On the other hand, graphite accumulations appear to be connected along shear lineaments over hundreds of meters or more. Structural, mineralogical, and geochemical studies suggest a tectonic model which explains the deposition of graphite as the relic and witness of a shearing process that occurred during the late Variscan (Upper Carboniferous) thrusting. This process took place while this part of the crust resided at temperatures between 240° and 380°C. Subsequent independent reverse faulting lifted this part to the Earth's surface. Our conclusion is that the KTB case indicates how high electrical conductivities in the upper crust, which originated from the middle to lower crust, are caused by graphite accumulations, rather than by fluids, and that these anomalies are related to shearing processes. Such graphite accumulations may exist elsewhere and may be of relevance in the context of present-day midcrustal conductors.
V. Haak and F. Simpson; A. Kontny [und 14 weitere]
Gesehen am 24.09.2020